1999
DOI: 10.1111/0022-4537.00143
|View full text |Cite
|
Sign up to set email alerts
|

Television and Prejudice Reduction: When Does Television as a Vicarious Experience Make a Difference?

Abstract: Televised role portrayals and interracial interactions, as sources of vicarious experience, contribute to the development of stereotypes, prejudice, and discrimination among children. The first section of this article reviews the amount and nature of racial/ethnic content on television, including limited portrayals of racial/ethnic groups and of interracial/ethnic interaction. The second section focuses on theoretical models that help explain television's role in the development, maintenance, and modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(35 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Recent literature has emphasized the importance of interaction content quality in outcome assessment (Graf et al, ; Lissitsa & Kushnirovich, ; Paolini et al, , ; Pettigrew et al, ). Research found different effects of positive and negative parasocial contact (Browne Graves, ; Mutz & Goldman, ; Theorin, ). Predominance of negative exposure can be linked to negative intergroup attitudes, while mostly positive portrayals of specific groups generated more positive attitudes toward those groups.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature has emphasized the importance of interaction content quality in outcome assessment (Graf et al, ; Lissitsa & Kushnirovich, ; Paolini et al, , ; Pettigrew et al, ). Research found different effects of positive and negative parasocial contact (Browne Graves, ; Mutz & Goldman, ; Theorin, ). Predominance of negative exposure can be linked to negative intergroup attitudes, while mostly positive portrayals of specific groups generated more positive attitudes toward those groups.…”
Section: Studymentioning
confidence: 99%
“…Recent literature has emphasized the importance of interaction content quality in outcome assessment (Graf et al, 2014;Lissitsa & Kushnirovich, 2018;Paolini et al, 2010Paolini et al, , 2014Pettigrew et al, 2011). Research found different effects of positive and negative parasocial contact (Browne Graves, 1999;Mutz & Goldman, 2010;Theorin, 2019).…”
Section: S Tudy 1 41 | Introduction To Study 1 and Research Hypothmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, though difficult to study systematically, the balance of the evidence suggests that school desegregation alone has been insufficient to reduce prejudice (Weinstein, Gregory, & Strambler, 2004). Media interventions such as Sesame Street have shown some evidence of promoting increased racial tolerance (Browne Graves, 1999), but they are not school based. Whole-school reform strategies focusing on democratic participation have shown benefits to children's social and emotional functioning (Battistich, Solomon, Watson, & Schaps, 1997;Solomon, Battistich, Watson, Schaps, & Lewis, 2000;Solomon, Watson, Battistich, Schaps, & Delucchi, 1996).…”
Section: Liberation Psychologymentioning
confidence: 99%
“…Information that (mis)represents a given state of affairs may endorse existing or create new stereotypes in the reader or viewer [3] which potentially impact their behavior. Cultivation theory has long suggested that prolonged exposure to biased information may shift individuals' perceptions over time [4] and even different gender ratios in image search results affect participants's perception of gender proportions in professions slightly but notably [17]. In respect to professions and gender, a potential effect is that in particular young people can be influenced in their career decisions, after being exposed to such information -conceivably avoiding an ostensibly (fe)male-dominated trade, even if they have a natural predisposition for it [8].…”
Section: Introductionmentioning
confidence: 99%